Does femoral morphology and stem alignment influence outcomes of cementless total hip arthroplasty with proximally coated double-tapered titanium stems?. Issue 3 (May 2021) - Narayanan, Rajkishen; Elbuluk, Ameer M; Chen, Kevin K; Eftekhary, Nima; Zuckerman, Joseph D; Deshmukh, Ajit J
Introduction: Stem subsidence and thigh pain can cause significant patient dissatisfaction after cementless THA. The purpose of this study was to examine the effect of proximal-femoral morphology and stem alignment on clinical outcomes using a double-tapered, cementless titanium femoral component. Methods: We retrospectively reviewed 281 consecutive, primary THAs from 2012 to 2014 with a mean follow-up of 4 years. Preoperative radiographs were used to assess femoral neck shaft angle (FNS), canal flare index (CFI), Dorr classification, and greater trochanter (GT) overhang. Postoperative radiographs were used to determine stem alignment and 6-week follow-up radiographs were used to determine subsidence. Clinical outcomes included thigh pain, leg-length discrepancy (LLD), patient-reported outcome measures (PROMs) and revision surgeries. Results: 271 stems (96%) did not subside (<4 mm) and 10 (4%) showed evidence of subsidence (>4 mm). Subsidence was significantly associated with subsequent revision surgery ( p < 0.01). 278 stems (99%) were in neutral alignment and 3 in varus (1%). Alignment did not significantly influence subsidence, thigh pain, LLD, revisions, or PROMs. Femoral morphology measures (FNS, CFI, Dorr classification, and GT overhang) were not significantly associated with stem alignment, subsidence, LLD, or revisions. CFI was significantly associated with intraoperative calcar fractures ( p = 0.02). GT overhang was associated with thigh pain ( p = 0.03) and FNS was inversely associated with postoperative HOOS scores. Conclusions: Subsidence and proximal-femoral morphology are potential sources of postoperative morbidity in certain cementless THA patients. In accordance with prior studies, CFI was identified as a potential risk factor for intraoperative calcar fractures. More research into preoperative femoral morphologies, such as GT overhang and FNS, is warranted as these may contribute to unsatisfactory results related to cementless THA.